Quality of sibling relationships and identity formation: Identification processes as a mediator - Ciptari Dhienda Aurellya; Darmawan Muttaqin (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
Identity formation is an adolescent developmental task that continues throughout life. Its process cannot be separated from the role of the significant person for adolescents, including siblings. Therefore, this study aims to examine the identification process (modeling and de-identification) as a mediator in the relationship between sibling relationships in identity formations commitment, in-depth exploration, and reconsideration of commitment. Four hundred adolescents aged 12-21 years participated in this study. The Indonesian version of the Utrecht-Management of Identity Commitments Scale (U-MICS), the Sibling Relationship Questionnaire (SRQ), and the Sibling Influence Scale (SIS) were used to measure identity formation, sibling relationship quality, and identification process. Data analysis was performed using regression analysis and the Sobel test. The results showed that the identification process could be a mediator between the quality of sibling relationships and identity formation. Also, the differences in quality among siblings lead adolescents to take different paths of the identification process, modeling, or de-identification, which impact the process of identity formation differences. Adolescents involved in modeling can learn and imitate older siblings to achieve an optimal identity. On the other hand, adolescents involved in de-identification find it more difficult and experience more challenges in achieving an optimal identity